English | Español

Try our Free Online Math Solver!

Online Math Solver

 

 

 

 

 

 

 

 
 
 
 
 
 
 
 
 

 

 

 
 
 
 
 
 
 
 
 

Please use this form if you would like
to have this math solver on your website,
free of charge.


Solutions to graded problems


Section 3.2

2. Using long division:

So P(x) = (3x-2)(x2-4)-12.

 

10. Write P(x) = 2x3-10x2-28x+60. Then we are told that x =-3 is a solution of the
equation P (x) = 0, which means that (x + 3) must be a factor of P(x), by the factor
theorem. We use long division to factor P :

So now the original equation is equivalent to
2(x + 3)(x2-8x + 10) = 0
(I pulled out a 2 for convenience.) To find the remaining two solutions of this equation
(apart from x =-3), we can use the quadratic formula on the second bracket:
(x2-8x + 10) = 0⇔
So the equation has solutions x =-3, x = 4-and x = 4 +.

16. We're told to use a graph to solve the equation x3-3x2-4x+12 = 0. This corresponds
to looking for x- intercepts of the graph y=x3-3x2-4x+12, sketched below:

From here, we can immediately read o that the x-intercepts are at (-2,0), (2,0)
and (3,0). By the factor theorem , this means we can write x3-3x2-4x+12=
(x-3)(x-2)(x + 2). So the original equation has solutions x =-2, x = 2 and x = 3.

 

28. How do we solve a cubic equation such as this one? First, collect all terms to one side:
x3 + 10x2 + 14x-60 = 0
From this point, our strategy is to inspect the graph and try to find at least one x -
intercept with rational coordinates (this is what we will do in general, for a polynomial
equation with degree≥3). The graph is sketched below:

On your calculators, you should use the calculate function to find the x-intercepts
(carefully!) I have drawn a zoomed -in graph (below) to show what happens near
x =-6.

From your calculator, you should find that the x-intercepts are at x =-6, x≈
-5.741657...and x≈1.741657...Obviously, the latter two are not exact. To find
them exactly, we can factor our polynomial, using the information that x =-6 is an
exact zero:

So x3-3x2-4x+12= 0 , (x+6)(x2 +4x-10) = 0 )⇒x =-6 or x =,
So the final, exact solutions are x =-6, x =-2-and x =-2 +

 

60. The information about the zeros gives that P(x) = a(x-1)2(x + 1)2. a is a stretching
factor that will be determined by the other piece of information: P(2) = 4 , 4 =
a(1)2(3)2 = 9a⇔a =.So P(x) =.

 

62. The graph shows that the polynomial P has zeros at x =-5, x = 2 and x = 5 (all
multiplicity one ), so we immediately have that P(x) = a(x-5)(x-2)(x + 5) (by the
factor theorem). To find the stretch factor a, we use one other point on the graph: in
this case, the y-intercept (0,50): P(0) = 50⇔50 = a(-5)(-2)(5) = 50a⇔a =
1. So P(x) = (x-5)(x-2)(x + 5).

 

Prev Next